Electrolyte for stabilizing sodium ion battery alloy negative electrode and battery system

By using ether solvents and additives to form an elastic SEI film in sodium ion batteries, the material powdering problem caused by changes in the volume of tin negative electrode is solved, the cycle life and capacity retention rate of the battery are improved, and the overall performance of the battery is enhanced.

CN119133600APending Publication Date: 2024-12-13NANJING UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311031286.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-16
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

In sodium ion batteries, the volume of the tin negative electrode changes greatly during the charging and discharging process, resulting in material powdering and loss of electrical contact. The prior art is difficult to effectively stabilize the alloy negative electrode, affecting the battery cycle performance and capacity retention rate.

Method used

Using an electrolyte containing ether solvents, additives and sodium salts, a thin and elastic SEI film is formed on the alloy negative electrode through ether solvents and additives, reducing the impact of volume expansion on SEI, and improving the stability and cycle life of the alloy negative electrode. .

Benefits of technology

It effectively slows down the SEI cracking and reconstruction process, improves the capacity retention and cycling performance of the tin negative electrode, extends the battery life time, and enhances the battery stability and charge and discharge efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133600A_ABST
    Figure CN119133600A_ABST
Patent Text Reader

Abstract

The invention relates to an electrolyte for stabilizing an alloy negative electrode of a sodium-ion battery and a battery system. The electrolyte comprises an ether solvent, an additive and sodium salt. The electrolyte contains the ether solvent, the additive and the sodium salt, and a thin and elastic SEI film can be formed on an alloy negative electrode through the ether solvent and the additive with a set structure, so that the influence of volume expansion of a negative electrode material on SEI is reduced, and the possibility of cracking and reconstruction of the SEI is reduced; a polymer film can be formed on the surface of the alloy negative electrode, and the stability and cycle life of the alloy negative electrode are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an electrolyte and a battery system, and in particular to an electrolyte and a battery system for stabilizing an alloy negative electrode of a sodium ion battery. Background Art

[0002] The concept of sodium-ion batteries was proposed in the 1980s but was later abandoned due to its lower energy density than lithium-ion batteries. The resurgence of sodium-ion technology in recent years relies on the low cost and natural abundance of sodium sources, which are about 30% lower in cost than lithium-ion batteries. Thanks to intensive research conducted in the past few years, researchers have been able to develop several high-performance sodium-ion battery cathode materials that are close to the current lithium-ion battery cathode in terms of specific capacity. As for the negative electrode, hard carbon is considered to be one of the most promising materials. However, it has a low reversible capacity of about 280 mAh g -1 , which is lower than the graphite negative electrode of lithium-ion batteries (372mAh g -1 ). In order to improve the energy density of sodium-ion batteries, it is urgent to develop anodes with high specific capacity. Alloy anodes, including tin, bismuth, and lead, have been widely studied due to their high specific capacity, but the toxicity of bismuth and lead makes them less promising in practical applications. In contrast, tin is an environmentally friendly material that is abundant in nature. Tin reacts with sodium to form Na 15 Sn4 alloy has a higher theoretical capacity (847 mAh g -1 ). Together with the existing positive electrode, it can form a sodium-ion battery with an energy density close to that of a classic lithium-ion battery.

[0003] The main problem that prevents the commercialization of tin anodes is that the tin anode undergoes a huge volume change of about 420% during the battery charge and discharge process, which can cause the material to pulverize, lose electrical contact, and peel off the material from the current collector. During the first charge and discharge process of the battery, the electrode material reacts with the electrolyte at the solid-liquid interface to form a passivation layer covering the surface of the electrode material, called the solid electrolyte interface (SEI). This layer of SEI breaks as the volume of tin expands, exposing the electrode. The electrode reacts with the electrolyte to form a new SEI. Therefore, the SEI is in a continuous process of breaking and reconstructing, which continuously consumes the sodium source and causes the capacity to decay rapidly. To solve this problem, the existing technologies include: (1) Controlling particle size. Tin nanodots (1-2 nm) are encapsulated in porous nitrogen-doped carbon nanofibers through electrospinning technology and heat treatment. In a sodium-tin half-cell, at 2000 mA g -1 The first week showed 530mAh g at high rate -1 The specific capacity is 483 mAh g even after 1300 cycles. -1The specific capacity of tin is only 10% of the capacity lost. Reducing the particle size of tin is an effective means to reduce the volume expansion of tin. However, after the particle size is reduced, due to the high specific surface area of ​​the nanomaterial, more SEI will be formed during the first charge and discharge process, consuming a large amount of sodium source, which causes the battery to show a lower first-week coulomb efficiency (70%). And because of the use of nanomaterials, their tap density is low, which will lead to a lower volume specific capacity of the battery. (2) Preparation of alloys of tin and other metals. Tin-copper alloy was prepared by a surfactant-assisted wet chemical method, and the nanocomposite material was used as the negative electrode material for sodium ion batteries. Copper improves the conductivity, hinders the expansion of tin, and buffers volume changes. The experimental results show that Sn 0.9 Cu 0.1 The nanoparticles can deliver more than 420 mA hg at a rate of 0.2C -1 The reversible capacity is as high as 97% after 100 cycles. However, in alloys composed of tin and other metals, the other metal does not provide capacity, which causes the material to exhibit a lower mass specific capacity. In addition, the preparation process of the alloy material is complicated and not suitable for industrial production. (3) Prepare tin composite materials and design unique structures. There are a lot of studies on the preparation of tin / carbon composite materials, which greatly improve the cycle stability by maintaining the integrity of the electrode. A material that encapsulates nano-tin in an eggshell-shaped carbon shell with a diameter of about 300nm was prepared. The sodium half-battery composed of this material has a high charge and discharge rate of 2000mA g -1 The first cycle discharge capacity is 550 mAh g -1 And maintain 430mA hg after 800 cycles -1 However, the complex preparation process and high cost make these methods unsuitable for practical applications. Therefore, a simple and economical method is urgently needed to stabilize the drastic volume change of alloy anodes such as micron tin during battery cycling. Summary of the invention

[0004] In order to solve the above problems, the present invention provides an electrolyte for stabilizing the alloy negative electrode of a sodium ion battery. The electrolyte contains an ether solvent, an additive and a sodium salt. A thin and elastic SEI film can be formed on the alloy negative electrode through the ether solvent and the additive with a set structure, thereby reducing the influence of the volume expansion of the negative electrode material on the SEI, thereby reducing the possibility of SEI rupture and reconstruction; a polymer film can be formed on the surface of the alloy negative electrode, thereby improving the stability and cycle life of the alloy negative electrode.

[0005] In order to solve the above problems, the technical solution adopted by the present invention is: an electrolyte for stabilizing the alloy negative electrode of a sodium ion battery, comprising an ether solvent, an additive and a sodium salt, wherein the sodium salt and the additive are both dissolved in the ether solvent, and the molecular formula of the additive is: X(O(CH2) n CH3)4, the structural formula is:

[0006]

[0007] Wherein X is a metal or non-metal element.

[0008] As a preferred embodiment, the additive is one of the following or a combination of both:

[0009]

[0010]

[0011] More preferably, the additive is

[0012] As a preferred solution, the total mass ratio of the additive to the sodium salt and the solvent is (0.01-80.0)%. Preferably, the total mass ratio of the additive to the sodium salt and the solvent is 5%.

[0013] As a preferred embodiment, the sodium salt is selected from at least one of NaCH3SO3 (sodium methanesulfonate), NaCF3SO3 (sodium trifluoromethanesulfonate), C4BNaO8 (sodium bis(oxalatoborate), C2BF2NaO4 (sodium difluorooxalatoborate), NaPO2F2 (sodium difluorophosphate), NaDFBP (sodium difluorobis(oxalatophosphate), NaPF6 (sodium hexafluorophosphate), NaClO4 (sodium perchlorate), NaSOCF3 (sodium trifluoromethanesulfonate), NaFSI (sodium bis(trifluoromethylsulfonyl imide), NaTFSI (sodium bis(trifluoromethylsulfonyl imide), NaBF4 (sodium tetrafluoroborate), NaNO3 (sodium nitrate), and NaAsF6 (sodium hexafluoroarsenate).

[0014] As a preferred embodiment, the sodium salt is NaPF6 (sodium hexafluorophosphate).

[0015] As a preferred solution, the concentration of the sodium salt in the electrolyte is 0.1M to 10M. More preferably, the concentration of the sodium salt in the electrolyte is 1M.

[0016] As a preferred solution, the solvent is a combination of one or more of DME (ethylene glycol dimethyl ether), DEGDME (diethylene glycol dimethyl ether), and TEGDME (tetraethylene glycol dimethyl ether).

[0017] As a preferred solution, the battery negative electrode is a micron tin negative electrode, and the additive or the solvent forms an elastic protective film on the surface of the micron tin negative electrode, and the protective film inhibits the expansion of the micron tin negative electrode.

[0018] On the other hand, the present invention provides a sodium ion battery system, comprising a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode is a layered metal oxide, polyanion, or Prussian blue sodium ion battery positive electrode material, the negative electrode is an alloy-type negative electrode material, preferably tin, and the electrolyte is an electrolyte prepared by any of the above schemes.

[0019] The present invention also provides a sodium ion battery system, comprising a positive electrode, a negative electrode and an electrolyte. The preparation method of the positive electrode is: micron tin, a conductive agent and an adhesive are uniformly mixed according to a mass ratio to form an electrode slurry with a certain viscosity, and the electrode slurry is coated on a copper foil current collector, and the coating amount is 1.5-2.0 mg cm -2 , after drying, cut into positive electrode sheets of sodium ion half-cells using a tablet press;

[0020] The negative electrode is prepared by: cutting sodium metal into thin slices in an argon-filled glove box as a negative electrode of the battery;

[0021] The electrolyte includes an ether solvent, an additive and a sodium salt, wherein the sodium salt is dissolved in the ether solvent, the additive has a molecular formula of XO4(CH2)4(CH3)4, and a structural formula of:

[0022] Wherein X is a metal or non-metal element.

[0023] As a preferred solution, the monomer particle size of the micron tin is 0.05-100 um.

[0024] In the electrolyte liquid phase, the additive will participate in the solvation structure of the sodium ion, that is, there will be several solvent molecules, anions of the sodium salt and additives around a sodium ion, and this structure is called a solvation sheath. At the interface between the electrolyte and the tin negative electrode, the solvation sheath will be desolvated, that is, the solvent molecules around the sodium ion, the anions of the sodium salt and the additive leave the sodium ion, and the sodium ion obtains electrons from the tin and alloys with the tin. At the interface, the solvent molecules, anions of the sodium salt, additives and free solvent molecules that escape from the solvation sheath may all be reduced by electrons, thereby attaching to the surface of the tin negative electrode to form SEI. Since the reduction potential of the sodium salt is higher than that of the additive, the anions of the sodium salt tend to be reduced to the inorganic components of the SEI first, and the additive tends to be reduced to the organic components of the SEI later. The short-chain organic components cannot maintain the elasticity of the SEI, and the volume expansion of the tin during the operation of the battery causes the SEI to rupture. In the present invention, the additive used can form an organic component of a long-chain polymer, so that the SEI has elasticity and can well maintain the integrity of the SEI.

[0025] The beneficial effects of the present invention include: (1) By using an ether electrolyte, the present invention enables the tin negative electrode to maintain a higher capacity during the cycle and has a better capacity retention rate, which means that the battery can provide a longer service life and more lasting performance.

[0026] (2) The thin and elastic SEI film formed between the electrolyte and the tin anode can effectively reduce the reaction between the tin anode and the electrolyte, delay the rupture and reconstruction process of the SEI, and thus slow down the rate of capacity decay.

[0027] (3) The polymerization of the additives causes the additives to form a polymer at the tin electrode / electrolyte interface. The polymer makes the SEI film more stable, which can effectively inhibit the expansion of the tin electrode, reduce the pulverization of the tin electrode material, and improve the cycle performance and stability of the battery.

[0028] (4) The synergistic effect of the components in the electrolyte inhibits the volume expansion of the tin electrode, thereby ensuring sufficient electrical contact between the tin electrode and the current collector. In addition, the tin electrode materials are in close contact with each other, ensuring smooth transmission of electrons and improving the battery's charge and discharge efficiency and long cycle life.

[0029] In summary, the present invention improves the cycle life and capacity retention rate of the battery, reduces the capacity decay rate, enhances the stability and cycle performance of the tin negative electrode, improves the stability of the tin electrode / electrolyte interface and inhibits the expansion of the tin electrode. These advantages effectively solve the problems of the tin negative electrode in the ester electrolyte, and improve the performance of the tin negative electrode and the overall performance of the sodium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 Schematic diagram of the tin electrode in Example 1 of the present invention after charging and discharging;

[0031] Figure 2 Schematic diagram of the tin electrode in Comparative Example 2 of the present invention after charge and discharge;

[0032] Figure 3 The cycle performance of the batteries in Comparative Example 1 and Comparative Example 2 of the present invention;

[0033] Figure 4 The cycle performance of the batteries in Example 1 and Comparative Example 3 of the present invention;

[0034] In the figure, 1. Solvation structure of ester electrolyte, 2. SEI membrane, 3. Solvation structure of ether electrolyte, 4. Current collector, 5. Tin electrode. DETAILED DESCRIPTION

[0035] The present invention is further explained in detail below in conjunction with the accompanying drawings and specific embodiments, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments.

[0036] The electrolyte for stabilizing the alloy negative electrode of a sodium ion battery in the present invention is proposed to solve the problem that the alloy negative electrode in a sodium battery is prone to material pulverization, loss of electrical contact, and easy peeling off on the current collector due to volume expansion. The electrolyte includes an ether solvent, an additive, and a sodium salt. The additive and the sodium salt are dissolved in the ether solvent, wherein the structural formula of the additive is as follows:

[0037] Wherein X is a metal or non-metal element.

[0038] Compounds of this structure can produce free radicals during the reduction and decomposition process of the electrolyte. The free radicals trigger the polymerization between the additive molecules, and then produce polymers on the surface of the negative electrode. The ether solvents in the electrolyte form a thin and elastic SEI (solid electrolyte interface membrane) film on the surface of the alloy negative electrode. The film has strong toughness and can still maintain stability even when facing a high-expansion battery negative electrode, reducing the impact of volume expansion on SEI and avoiding breakage of the negative electrode material.

[0039] In some embodiments, the additive X is a tetravalent element, and the additive may be (hereinafter referred to as TEOS) or (hereinafter referred to as: TEOT) or a combination of the two, preferably The additive does not react with the electrode material tin negative electrode, and can generate a polymer at the tin negative electrode to inhibit the expansion of the negative electrode material.

[0040] In some embodiments, based on the total amount of sodium salt and solvent, the amount of additive added is (0.01-80)%, preferably (0.1-40)%, and more preferably (3-10)%. If it is too low, effective polymer cannot be generated to protect the alloy negative electrode. If it is too high, the sodium salt concentration will be low, affecting the battery efficiency. The optional ratio is 0.1%, 1%, 2%, 3%, 4%, 5%, preferably 5%. At this ratio, the battery efficiency can reach 700 mAh g after 100 cycles, and the specific capacity is still maintained at 700 mAh g -1 As shown above, compared with the initial state, the specific capacity has no significant decrease, and good battery stability is maintained.

[0041] In some embodiments, the ether solvent in the additive is selected from one or more combinations of DME (ethylene glycol dimethyl ether), DEGDME (diethylene glycol dimethyl ether), TEGDME (tetraethylene glycol dimethyl ether), preferably DME (ethylene glycol dimethyl ether). Such solvents and additives work together to form a highly elastic SEI film on the negative electrode material on the one hand, and further assemble polymers on the SEI film on the other hand, enhance the strength and toughness of the protective film, enhance the stability of the electrode / electrolyte interface, inhibit the expansion of the tin electrode material, and thus improve the cycle performance of the battery. Ether solvents have a low reduction potential, and the chain length of the reduction product is relatively long. Ether electrolyte solvents tend to be reduced after more anions are reduced, which helps to form an inner layer of inorganic reduction products dominated by anions, and an outer layer of organic reduction products dominated by solvent molecules. The inner layer of inorganic products has low adhesion to the alloy surface, so that SEI can migrate on the interface to adapt to volume changes; the outer layer of polymers has a certain elasticity and modulus, which can adapt to the continuous changes in the volume of the tin negative electrode.

[0042] In some embodiments, the sodium salt in the electrolyte is selected from at least one of NaCH3SO3 (sodium methanesulfonate), NaCF3SO3 (sodium trifluoromethanesulfonate), C4BNaO8 (sodium bis(oxalatoborate), C2BF2NaO4 (sodium difluorooxalatoborate), NaPO2F2 (sodium difluorophosphate), NaDFBP (sodium difluorobis(oxalatophosphate), NaPF6 (sodium hexafluorophosphate), NaClO4 (sodium perchlorate), NaSOCF3 (sodium trifluoromethanesulfonate), NaFSI (sodium bis(trifluoromethylsulfonylimide), NaTFSI (sodium bis(trifluoromethylsulfonylimide), NaBF4 (sodium tetrafluoroborate), NaNO3 (sodium nitrate), and NaAsF6 (sodium hexafluoroarsenate), preferably NaPF6 (sodium hexafluorophosphate). This sodium salt has a large radius anion and weak association between anions and cations, which can ensure sufficient sodium salt solubility and ion transport performance. It is easily soluble in ether solvents to form a uniform electrolyte. This sodium salt can avoid irreversible chemical reactions during battery operation and has good chemical stability, thereby reducing the life of the battery.

[0043] When configuring the electrolyte, the concentration of sodium salt has an important influence on the battery performance and the performance of forming the electrode / electrolyte interface. When the sodium salt concentration is low, the electrolyte has a low ionic conductivity due to the lack of charge carriers. In low-concentration electrolytes, there are more solvent molecules involved in coordination, and the number of free solvents that do not participate in coordination is also large, making the electrolyte / electrode interface and the ion conduction in the electrolyte largely dependent on the inherent properties of the solvent. More importantly, in low-concentration electrolytes, when the solvated sodium ions move toward the negative electrode, the scarce anions in the electrolyte are more likely to be depleted on the negative electrode side, causing a large polarization. On the contrary, when the sodium ion concentration increases to a certain value, further increase in concentration will cause a reduction in free solvent molecules and coordinated solvent molecules, resulting in significant ion aggregation, thereby reducing ion mobility, which is manifested macroscopically as an increase in electrolyte viscosity. However, the function of the electrolyte will not only be limited to achieving rapid ion migration, but also need to simultaneously achieve passivation of the electrode, that is, to form a stable SEI. When the electrolyte concentration is high, the number of anions in the electrolyte is high, and the proportion of solvent molecules will be greatly reduced. The solvent molecules will be largely involved in the coordination with the cations. Therefore, the free solvent molecules in the electrolyte will be greatly reduced or even disappear. At the same time, the anions are also largely involved in the coordination with the cations. Due to the high anion reduction potential, the anions can be decomposed first to form a dense, inorganic-rich solid electrolyte interface film. As a result, the chemical and electrochemical stability of the electrolyte and the tin negative electrode are greatly enhanced. However, the higher the sodium ion concentration, the better. The electrolyte with a higher sodium ion concentration has a large viscosity and limited ion diffusion. Therefore, there is a preferred sodium salt concentration range. The concentration of NaPF6 in the electrolyte can be set to 0.1M~10M, generally (0.5~1.5)M. In some embodiments, the sodium salt concentration is 0.5M, 0.75M, 1M, 1.25M, 1.5M, and preferably 1M. This concentration, on the one hand, makes the electrolyte have a high ionic conductivity, and on the other hand, makes the sodium salt have a high ion diffusion coefficient in the electrolyte liquid phase.

[0044] The present invention provides a sodium battery system, comprising a positive electrode, a negative electrode and an electrolyte, wherein the electrolyte is the electrolyte obtained by the above method, the negative electrode is an alloy negative electrode, preferably tin, and during the battery charging and discharging process, the negative electrode material tin forms an alloy with sodium, or de-alloys, and the positive electrode material is sodium vanadium phosphate.

[0045] In order to verify the role of the electrolyte in the above battery system, a half-battery system was constructed for testing. The sodium ion half-battery system includes a positive electrode, a negative electrode and an electrolyte. The electrolyte is the electrolyte obtained by the above method. The preparation method of the positive electrode is:

[0046] Micronized tin, conductive agent SuperP and adhesive CMC (sodium carboxymethyl cellulose) were mixed evenly in a mass ratio of 7:2:1 to form an electrode slurry with a certain viscosity, which was then coated on the copper foil current collector with a coating amount of 1.5-2.0 mg cm -2 After drying at 120°C, it is cut into discs with a diameter of 14 mm using a tablet press to make the positive electrode sheets of the sodium ion half-cell that meet the requirements.

[0047] The negative electrode was prepared by cutting sodium metal into thin sheets with a diameter of 16 mm and a thickness of about 50 um in an argon-filled glove box.

[0048] The reasons for selecting the positive and negative electrode materials are: tin and sodium form Na 15 Sn4 alloy, with high theoretical capacity.

[0049] The following is further described by way of specific embodiments

[0050] Example 1 (containing additives and ether electrolyte)

[0051] Electrolyte: contains solvent, additive and sodium salt, the solvent is TEGDME (tetraethylene glycol dimethyl ether), the sodium salt is NaBF4, and the additive is TEOS.

[0052] The electrolyte is used in a sodium ion half-cell system, which includes a positive electrode, an electrolyte and a negative electrode. The positive electrode is prepared by mixing micron tin, a conductive agent SuperP and a binder CMC (sodium carboxymethyl cellulose) in a mass ratio of 7:2:1 to form an electrode slurry with a certain viscosity, and coating it on a copper foil current collector with a coating amount of 1.5 to 2.0 mg cm -2 After drying at 120°C, it is cut into discs with a diameter of 14 mm using a tablet press to make the positive electrode sheets of the sodium ion half-cell that meet the requirements.

[0053] The negative electrode was prepared by cutting sodium metal into thin sheets with a diameter of 16 mm and a thickness of about 50 um in an argon-filled glove box.

[0054] The electrolyte is prepared by mixing the solvent TEGDME with an appropriate amount of sodium salt NaBF4 so that the concentration of the sodium salt in the formed electrolyte is 1 M. After the sodium salt is completely dissolved, an appropriate amount of additive TEOS is added so that the mass of the additive accounts for 5% of the total mass of the solvent and the sodium salt.

[0055] Preparation of sodium ion half-cell: In an argon-filled glove box, the positive electrode, negative electrode, and electrolyte prepared according to the above process were assembled into a button cell with a diameter of 20 mm and a height of 3.2 mm.

[0056] Comparative Example 1 (containing ether solvent DME)

[0057] Electrolyte: includes solvent and sodium salt, wherein the solvent is DME and the sodium salt is NaPF6.

[0058] The above electrolyte is used in a sodium ion half-cell system, which includes a positive electrode, a negative electrode and an electrolyte, wherein the preparation methods of the positive electrode and the negative electrode are the same as in Example 1, and the electrolyte is configured as follows: the solvent DME is mixed with an appropriate amount of sodium salt NaPF6 so that the concentration of the sodium salt in the electrolyte is 1M.

[0059] Preparation of sodium ion half-cell: In an argon-filled glove box, the positive electrode, negative electrode, and electrolyte prepared according to the above process were assembled into a button cell with a diameter of 20 mm and a height of 3.2 mm.

[0060] Comparative Example 2 (ester solvent PC)

[0061] Electrolyte: includes solvent and sodium salt, wherein the solvent is PC (propylene carbonate) and the sodium salt is NaPF6.

[0062] The above electrolyte is used in a sodium ion half-cell system, which includes a positive electrode, a negative electrode and an electrolyte, wherein the preparation methods of the positive electrode and the negative electrode are the same as in Example 1, and the configuration method of the electrolyte is: mixing the solvent PC (propylene carbonate) with an appropriate amount of sodium salt NaPF6, and the concentration of NaPF6 in the solution is 1M.

[0063] Preparation of sodium ion half-cell: In an argon-filled glove box, the positive electrode, negative electrode, and electrolyte prepared according to the above process were assembled into a button cell with a diameter of 20 mm and a height of 3.2 mm.

[0064] Comparative Example 3 (containing ether solvent TEGDME)

[0065] Electrolyte: comprising a solvent and a sodium salt, wherein the solvent is TEGDME and the sodium salt is NaBF4.

[0066] The above electrolyte is used in a sodium ion half-cell system, which includes a positive electrode, a negative electrode and an electrolyte, wherein the preparation methods of the positive electrode and the negative electrode are the same as in Example 1, and the preparation method of the electrolyte is: the solvent TEGDME is mixed with an appropriate amount of sodium salt NaBF4, and the concentration of the sodium salt in the solution is 1M.

[0067] Preparation of sodium ion half-cell: In an argon-filled glove box, the positive electrode, negative electrode, and electrolyte prepared according to the above process were assembled into a button cell with a diameter of 20 mm and a height of 3.2 mm.

[0068] The performance of the sodium ion half-cell obtained in Example 1 and Comparative Examples 1-3 was tested. The battery testing process was as follows: first, the battery was discharged at a constant current of 0.1C to 0.01V, and the discharge capacity was recorded as C1. Then, the battery was charged at a constant current of 0.1C to 2V, and the charge capacity was recorded as C2. The battery was cycled for 3 cycles to activate the battery. Starting from the fourth cycle, the battery was discharged at a constant current of 0.5C to 0.01V, and then charged at a constant current of 0.5C to 2V, and the cycle was repeated for 97 cycles. The discharge capacity at this time was recorded as C3. The ICE (first coulomb efficiency) and capacity retention rate were calculated according to the following formula:

[0069] ICE=C2 / C1*100%

[0070] Capacity retention rate = C3 / C1*100%

[0071] Stability test of tin with ester and ether electrolytes: The tin electrode material was assembled into batteries with ether electrolyte NaPF6 inDME, commercial carbonate electrolyte NaPF6 in PC, NaPF6 in TEGDME+5wt%TEOS, and NaPF6 in TEGDME for cycle testing, and the cycle life and capacity attenuation were recorded, such as Figure 2 and Figure 3 As shown; and observe the stability of the tin electrode in Example 1 and Comparative Example 2 after 100 charge and discharge cycles, as Figure 1 and Figure 2 As shown by Figure 1 It can be seen that the tin electrode 5 corresponding to the electrolyte containing ether solvents and additives has no obvious breakage phenomenon, the ether electrolyte solvation structure 3 is stable, the tin electrode 5 and the current collector 4 still have good contact stability, and the SEI film 2 is thin and not damaged; Figure 2 It can be seen that the tin electrode 5 corresponding to the ester electrolyte solvation structure 1 expands and breaks, the tin electrode 5 is separated from the current collector 4, and the SEI film 2 is thick and cracked.

[0072] Figure 2 The discharge capacity of the half-cell assembled by the two electrolytes per cycle is shown in Table 2. The commercial ester electrolyte (1M NaPF6 in PC) in Comparative Example 2 had a large capacity decay in the initial stage. Only 621 mAh g was discharged in the first cycle. -1 The capacity is much lower than the theoretical specific capacity of tin, 847 mAh g -1 . And after the 5th cycle, the capacity decayed to almost 0. This shows that commercial ester electrolytes cannot be applied to tin negative electrodes. However, the ether electrolyte (1M NaPF6 in DME) in Comparative Example 1 can stabilize the tin negative electrode well. Its ICE is as high as 88%, and the capacity decay is relatively slow. After 100 cycles, there is still 651mAh g -1The capacity retention rate is 73.5%. Although ether electrolytes have a certain stabilizing effect on the capacity of the tin negative electrode compared with ester electrolytes, there is still a large gap from the theoretical capacity.

[0073] Figure 3 It represents the discharge capacity per cycle of the half-cell assembled with two electrolytes in Example 1 and Comparative Example 3. Figure 3 It can be seen that the present invention further stabilizes the tin electrode on the basis of stabilizing the tin electrode with the ether electrolyte by adding an additive that inhibits the expansion of the tin electrode. The TEOS additive polymerizes on the tin surface to form a stable protective film on the tin electrode surface, thereby improving the stability of the silicon negative electrode / electrolyte interface and the stability of the tin electrode / electrolyte interface. By inhibiting the expansion of the tin electrode material, the pulverization phenomenon of the tin electrode material is improved, the battery cycle performance is greatly improved, and the excellent performance of the sodium ion battery is ensured.

[0074] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention.

Claims

1. An electrolyte for stabilizing a sodium ion battery alloy negative electrode, characterized in that: It includes an ether solvent, an additive and a sodium salt, wherein the sodium salt is dissolved in the ether solvent, and the molecular formula of the additive is: XO4(CH2) 4n (CH3)4, the structural formula is: Wherein X is a metal or non-metal element.

2. The electrolyte for stabilizing the alloy negative electrode of a sodium ion battery according to claim 1, characterized in that: The additive is one of the following or a mixture of two:

3. The electrolyte for stabilizing the alloy negative electrode of a sodium ion battery according to claim 1, characterized in that: The additive is soluble in the ether solvent, and the total mass ratio of the additive to the sodium salt and the ether solvent is (0.01-80.0)%.

4. The electrolyte for stabilizing the alloy negative electrode of a sodium ion battery according to claim 1, characterized in that: The total mass ratio of the additive to the sodium salt and the solvent is 5%.

5. The electrolyte for stabilizing the alloy negative electrode of a sodium ion battery according to claim 1, characterized in that: The sodium salt is selected from at least one of NaCH3SO3 (sodium methanesulfonate), NaCF3SO3 (sodium trifluoromethanesulfonate), C4BNaO8 (sodium bis(oxalatoborate), C2BF2NaO4 (sodium difluorooxalatoborate), NaPO2F2 (sodium difluorophosphate), NaDFBP (sodium difluorobis(oxalatophosphate), NaPF6 (sodium hexafluorophosphate), NaClO4 (sodium perchlorate), NaSOCF3 (sodium trifluoromethanesulfonate), NaFSI (sodium bis(trifluoromethylsulfonyl imide), NaTFSI (sodium bis(trifluoromethylsulfonyl imide), NaBF4 (sodium tetrafluoroborate), NaNO3 (sodium nitrate), and NaAsF6 (sodium hexafluoroarsenate).

6. The electrolyte for stabilizing the alloy negative electrode of a sodium ion battery according to claim 5, characterized in that: The sodium salt is NaPF6 (sodium hexafluorophosphate).

7. The electrolyte for stabilizing the alloy negative electrode of a sodium ion battery according to claim 1, characterized in that: The concentration of the sodium salt in the electrolyte is 0.1M to 10M.

8. The electrolyte for stabilizing the alloy negative electrode of a sodium ion battery according to claim 1, characterized in that: The concentration of the sodium salt in the electrolyte is 1M.

9. The electrolyte for stabilizing the alloy negative electrode of a sodium ion battery according to claim 1, characterized in that: The solvent is a combination of one or more of DME (ethylene glycol dimethyl ether), DEGDME (diethylene glycol dimethyl ether), and TEGDME (tetraethylene glycol dimethyl ether).

10. The electrolyte for stabilizing the alloy negative electrode of a sodium ion battery according to claim 1, characterized in that: The battery negative electrode is a tin negative electrode, and the additive or the solvent forms an elastic protective film on the surface of the tin negative electrode, and the protective film inhibits the expansion of the tin negative electrode.

11. A sodium ion battery system, comprising a positive electrode, a negative electrode and an electrolyte, characterized in that: The electrolyte is the electrolyte according to any one of claims 1 to 10.